Assessment of postoperative renal function after adrenalectomy in patients with primary aldosteronism. (1st November 2018) - Onohara, Tadashi; Takagi, Toshio; Yoshida, Kazuhiko; Iizuka, Junpei; Okumi, Masayoshi; Kondo, Tsunenori; Ishida, Hideki; Tanabe, Kazunari
Abstract : Objective: To investigate kidney function change during adrenalectomy in patients with primary aldosteronism and assess predictors of kidney function decline. Methods: The present study included 90 patients who underwent adrenalectomy for primary aldosteronism between 2004 and 2017. Kidney function was evaluated 1 month after surgery. Predictors associated with a ≥10% decline in the estimated glomerular filtration rate were investigated. Kidney parenchymal volume was compared before and after surgery in 10 patients using volumetric studies. Results: The mean estimated glomerular filtration rate decline in the total cohort at 1 month after surgery was 13.3% (before: 72.9 mL/min/1.73 m 2, after: 64.9 mL/min/1.73 m 2, P  < 0.0001). The mean serum plasma aldosterone concentration (before: 373 pg/mL vs after: 78 pg/mL, P  < 0.0001) and potassium level (before: 3.7 mEq/L vs after: 3.9 mEq/L, P  = 0.0001) were also significantly different after surgery. Age (odds ratio 6.37, P  = 0.0006), preoperative plasma aldosterone concentration (odds ratio 3.12, P  = 0.0209) and preoperative serum potassium level (odds ratio 2.87, P  = 0.0010) were independent predictors of a ≥10% decline in estimated glomerular filtration rate. Volumetric studies in 10 patients showed that mean postoperative parenchymal volume was significantly decreased compared with the preoperative volume (263 cc vs 312 cc, P  = 0.0003), with decreases in estimated glomerular filtration rate from 63 to 56 mL/min/1.73 m 2 ( P  = 0.0146). Conclusions: Kidney function deterioration after adrenalectomy can be detected in patients with primary aldosteronism. Age, preoperative plasma aldosterone concentration and preoperative potassium level are significant predictors of a decrease in the estimated glomerular filtration rate. Normal parenchymal volume decreases in line with renal functional deterioration.